The urban informal economy, local inclusion and achieving a global green transformation. (April 2016) - Brown, Donald; McGranahan, Gordon
Abstract: The green economy is widely promoted as a 21st century solution to sustainable development. The role of cities in pursuing this agenda is increasingly recognised. Yet, the informal economy, which so many urban dwellers and workers in low- and middle-income countries depend upon, is seldom considered. This paper examines the opportunities and barriers that the urban informal economy pose for making economies greener, and the risks that such attempts pose for vulnerable informal dwellers and workers. In contemplating how this group can be included in the transition to a greener economy, the different schools of thought on informality are reviewed, with a focus on recent thinking that relates urban informality to conflicting processes of inclusion and exclusion. The paper then considers a set of action areas aimed at leveraging the positive contributions that informal dwellers and workers can make in the transition to an economy that is not only greener, but also more inclusive. Leveraging these contributions will require recognising and supporting women's unpaid reproductive work (including community organising and strategizing around environmental improvements) and applying the principles of inclusive urban planning. Highlights: The global environmental agendas must engage with the urban informal economy. Greening the formal economy risks shifting anti-green activities to the informal economy. Centralized regulation of the informal economy risks amplifying local exclusion. Greening the informal economy inclusively should involve representative organizations.